2016
DOI: 10.1016/j.msea.2015.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Determining individual phase properties in a multi-phase Q&P steel using multi-scale indentation tests

Abstract: a b s t r a c tA new inverse method was developed to predict the stress-strain behaviors of constituent phases in a multi-phase steel using the load-depth curves measured in nanoindentation tests combined with microhardness measurements. A power law hardening response was assumed for each phase, and an empirical relationship between hardness and yield strength was assumed. Adjustment was made to eliminate the indentation size effect and indenter bluntness effect. With the newly developed inverse method and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 75 publications
0
35
0
Order By: Relevance
“…Nanoindentation is a small-scale in-situ testing and characterization method which has been widely used for coatings, thin films and bulk polycrystalline materials [26][27][28][29][30][31][32].…”
Section: Mechanical Property Of Coatingsmentioning
confidence: 99%
“…Nanoindentation is a small-scale in-situ testing and characterization method which has been widely used for coatings, thin films and bulk polycrystalline materials [26][27][28][29][30][31][32].…”
Section: Mechanical Property Of Coatingsmentioning
confidence: 99%
“…33 HV0.1) can be mainly related to the inhomogeneous distribution of martensite, bainite, retained austenite and precipitates in these regions. In other words, different constituents in multiphase steels have different hardness and their volume fraction and distribution can change the overall hardness [39,40] . It can be thus inferred that the most likely reasons for the high hardness of Steel 2 was attributed to the martensite/bainite volume fraction and also precipitation strengthening.…”
Section: Vickers Hardnessmentioning
confidence: 99%
“…Also, previous studies have demonstrated that annealing-induced hardening might be possible in bulk metallic glasses (BMG) [9] [15]. Multi-scaling indentation as well as different inverse methods can be utilized to access the elastic properties [16] and plastic properties of individual grains [17] [18] and individual phases [19]. Besides, the application of multi-direction indentation will be helpful to understand the possible anisotropy of REMGs foils [20].…”
Section: Introductionmentioning
confidence: 99%